Diagnosing Masked Hypertension Using Ambulatory Blood Pressure Monitoring, Home Blood Pressure Monitoring, or Both?. Issue 5 (November 2018) - Anstey, D. Edmund; Muntner, Paul; Bello, Natalie A.; Pugliese, Daniel N.; Yano, Yuichiro; Kronish, Ian M.; Reynolds, Kristi; Schwartz, Joseph E.; Shimbo, Daichi
Abstract : Guidelines recommend measuring out-of-clinic blood pressure (BP) to identify masked hypertension (MHT) defined by out-of-clinic BP in the hypertensive range among individuals with clinic-measured BP not in the hypertensive range. The aim of this study was to determine the overlap between ambulatory BP monitoring (ABPM) and home BP monitoring (HBPM) for the detection of MHT. We analyzed data from 333 community-dwelling adults not taking antihypertensive medication with clinic BP <140/90 mm Hg in the IDH study (Improving the Detection of Hypertension). Any MHT was defined by the presence of daytime MHT (mean daytime BP ≥135/85 mm Hg), 24-hour MHT (mean 24-hour BP ≥130/80 mm Hg), or nighttime MHT (mean nighttime BP ≥120/70 mm Hg). Home MHT was defined as mean BP ≥135/85 mm Hg on HBPM. The prevalence of MHT was 25.8% for any MHT and 11.1% for home MHT. Among participants with MHT on either ABPM or HBPM, 29.5% had MHT on both ABPM and HBPM; 61.1% had MHT only on ABPM; and 9.4% of participants had MHT only on HBPM. After multivariable adjustment and compared with participants without MHT on ABPM and HBPM, those with MHT on both ABPM and HBPM and only on ABPM had a higher left ventricular mass index (mean difference [SE], 12.7 [2.9] g/m 2, P <0.001; and 4.9 [2.1] g/m 2, P =0.022, respectively), whereas participants with MHT only on HBPM did not have an increased left ventricular mass index (mean difference [SE], −1.9 [4.8] g/m 2, P =0.693). These data suggest that conducting ABPM will detect many individuals with MHT who have an increased cardiovascular disease risk. Abstract : Supplemental Digital Content is available in the text.